PENGARUH MOTIVASI, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. ASDP INDONESIA FERRY (PERSERO) CABANG BALIKPAPAN - Faisal Wardana; Tamzil Yusuf; Imam Arrywibowo (MEDIA RISET EKONOMI [MR.EKO], 2022)
The purpose of this study was to determine the effect of Motivation, Discipline and Work Environment on Employee Performance PT. ASDP Indonesia Ferry (Persero) in Balikpapan. The population in this study were permanent employees as much as 222 respondents. By using random sampling techniques so the sample that is in use as much as   83 respondents.   Data   collection   techniques   are   observation,   interviews   and questionnaires. The data analysis technique used is Multiple Linear Regression using program SPSS v22. The results showed motivation, discipline and work environment simultaneously affect the performance of employees PT. ASDP Indonesia Ferry (Persero) in Balikpapan. Work environment partially had significant influence and dominant to the performance of employees PT. ASDP Indonesia Ferry (Persero) in Balikpapan.